Suberoylanilide hydroxamic acid represses glioma stem-like cells - Hsu, Che-Chia (J Biomed Sci, 2016)
BACKGROUND: Glioma stem-like cells (GSCs) are proposed to be responsible for high resistance in glioblastoma multiforme (GBM) treatment. In order to find new strategies aimed at reducing GSC stemness and improving GBM patient survival, we investigated the effects and mechanism of a histone deacetylases (HDACs) inhibitor, suberoylanilide hydroxamic acid (SAHA), since HDAC activity has been linked to cancer stem-like cell (CSC) abundance and properties. METHODS: Human GBM cell lines were plated in serum-free suspension cultures allowed for sphere forming and CSC enrichment. Subsequently, upon SAHA treatment, the stemness markers, cell proliferation, and viability of GSCs as well as cellular apoptosis and senescence were examined in order to clarify whether inhibition of GSCs occurs. RESULTS: We demonstrated that SAHA attenuated cell proliferation and diminished the expression stemness-related markers (CD133 and Bmi1) in GSCs. Furthermore, at high concentrations (more than 5 μM), SAHA triggered apoptosis of GSCs accompanied by increases in both activation of caspase 8- and caspase 9-mediated pathways. Interestingly, we found that a lower dose of SAHA (1 μM and 2.5 μM) inhibited GSCs via cell cycle arrest and induced premature senescence through p53 up-regulation and p38 activation. CONCLUSION: SAHA induces apoptosis and functions as a potent modulator of senescence via the p38-p53 pathway in GSCs. Our results provide a perspective on targeting GSCs via SAHA treatment, and suggest that SAHA could be used as a potent agent to overcome drug resistance in GBM patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12929-016-0296-6) contains supplementary material, which is available to authorized users.